Women's Safety and Gender-Based Violence in the Republic of North Macedonia - Tozija, Fimka (Frontiers in Public Health, 2020)
• Introduction: Violence against women in Republic of North Macedonia is the most common form of human rights violation and thus women’s safety is a public health problem of high priority. • Policy Implications: There are significant achievements in: pol-icy development; legislation harmonization for prevention of violence against women and pro-tocols for treatment and support of female victims and collabora-tion and coordination of different sectors. • Actionable Recommendations: In practice, still, there is a need to establish a system of institutions for effective prevention, protec-tion, evidence and support of women victims of gender based violence and prosecution of per-petrators. • Conclusions: Policies for women’s safety improvement should be considered as priority and undertaken at individual, re-lationship, community and soci-ety level.